Classical music policy and practise in a British city - Wang, Juan (2011)
The argument in my thesis regarding cultural policy points out a fundamental contradiction about the nature of democracy. The impulse that should motivate public cultural policies is primarily democratic: it is to give universal access to what are deemed unique cultural practices. However, these practices are often socially and culturally inaccessible. For instance, in the case of the high arts and the world of classical music, works are often prized precisely because of their high degree of sophistication within a particular tradition, something that tends to prevent such works from being immediately understood or enjoyed by the general public. Therefore, it seems, an effective cultural policy is crucial to offer universal access to unique cultural practices, like classical music. Based on the theoretical work of Jim McGuigan (drawing upon Habermas's notion of the public sphere) and of Tony Bennett (drawing upon Foucault's notion of governmentality), my research starts at a local city level in a British context, and then focuses on the relationship between classical music and cultural policy. I also pose the question of how the value implicit in a ‘culture in common’ and the plural forms of cultural expression help the development of self-respect and esteem and thus contribute to democratic values in a British context. My thesis is designed to contribute to a critical understanding of how classical music policy has been exercised at a local level. This has been achieved by adopting a qualitative research approach. Thus, my research findings show that power differentials exist in the field of cultural policy. The research focus in this thesis suggests that music policy might focus too much on the imposition of a top-down model that is unable to deal adequately with the dispersion of power. Further, the current debate does not take into account the importance of tradition and the critical role of multiculturalism. The theory points to ways these features can be incorporated into future debates on cultural policy.